The Evaluative Process Model of Objectification: how men's evaluations of patriarchal security and women's fit with conventional beauty and sexuality norms interact to predict perpetration of sexually objectifying behaviors - Sáez, Gemma; Riemer, Abigail R.; Klein, Olivier; Gervais, Sarah J. (Frontiers in Social Psychology, 2025)
Scholars have expanded upon the original scope of Objectification Theory, but theoretical and empirical research on objectification from the perceiver perspective remains underdeveloped. The literature focused on the perceiver perspective has narrowly focused on objectification perpetrated toward extremely attractive and sexualized women, despite objectification being a universal experience amongst all women. In the current paper, we propose the Evaluative Process Model of Objectification (EPO) to predict who sexually objectifies and why women are treated as sexual objects, to then answer toward whom and how sexual objectification may be directed. In particular, the EPO considers perceived attributes of female targets in conjunction with male perceivers' feelings of power. Extending Objectification Theory's suggestion that objectification is pervasive because of the patriarchal cultures women live in, the EPO suggests that objectification is instrumental in men's attempts to preserve and regain their position within the patriarchy. Among men who endorse patriarchal ideologies, perceived patriarchy threat or security is theorized to interact with evaluations of female targets to predict whether objectifying perceptions of female targets result in benevolent, derogative, or dismissive objectifying behaviors. After articulating the EPO, we propose hypotheses to be tested in future research and conclude with a discussion of theoretical and practical implications.